Advances in diagnosis and treatment of vestibular migraine and the vestibular disorders it mimics - Nicholas E.F. Hac; Daniel R. Gold (Neurotherapeutics)
Dizziness is one of the most common chief complaints in both the ambulatory care setting and the emergency department. These symptoms may be representative of a broad range of entities. Therefore, any attempt at treatment must first start with determining the etiology. In this current perspective, we focus specifically on the diagnosis of and treatment of vestibular migraine, which is common and overlaps clinically with a variety of other diagnoses. We discuss the traditional treatments for vestibular migraine in addition to the recent explosion of novel migraine therapeutics. Because vestibular migraine can mimic, or co-exist with, a variety of other vestibular diseases, we discuss several of these disorders including persistent postural-perceptual dizziness, benign paroxysmal positional vertigo, post-concussive syndrome, Ménière's disease, and cerebrovascular etiologies. We discuss the diagnosis of each, as well as overlapping and distinguishing clinical features of which the reader should be aware. Finally, we conclude with evidence based as well as expert commentary on management, with a particular emphasis on vestibular migraine.